Techography. Intrauterine localization of copper T-type devices by transabdominal sonogram - Muñoz Delgado, Saulo; Valencia, Luis Fernando; Villa R., Ivonne; Valdivieso, Hernando; Sánchez, Alvaro (Colombia Medica, 1990)
Pathology associated with IUDs has been reported in several publications. This paper describes an echographic technique called T-echography because it provides an objective localization of the IUD concerning longitudinal and transversal diameters of the uterus. This technique applies to the copper T. In the present study, only 55% of IUDs had optimal situations. Tecography should be performed two weeks after the device is applied. There is a close correlation between pathological syndromes and geography, permitting adequate handling of patients, even IUD withdrawal, if it is necessary.